Subglacial environments and the search for life beyond the earth - Cockell, C.; Bagshaw, E.; Balme, M.; Doran, P.; McKay, C.; Miljkovic, Katarina; Pearce, D.; Siegert, M.; Tranter, M.; Voytek, M.; Wadham, J. (American Geophysical Union, 2011)
One of the most remarkable discoveries resulting from the robotic and remote sensing exploration of space is the inferred presence of bodies of liquid water under ice deposits on other planetary bodies: extraterrestrial subglacial environments. Most prominent among these are the ice-covered ocean of the Jovian moon, Europa, and the Saturnian moon, Enceladus. On Mars, although there is no current evidence for subglacial liquid water today, conditions may have been more favorable for liquid water during periods of higher obliquity. Data on these extraterrestrial environments show that while they share similarities with some subglacial environments on the Earth, they are very different in their combined physicochemical conditions. Extraterrestrial environments may provide three new types of subglacial settings for study: (1) uninhabitable environments that are more extreme and life-limiting than terrestrial subglacial environments, (2) environments that are habitable but are uninhabited, which can be compared to similar biotically influenced subglacial environments on the Earth, and (3) environments with examples of life, which will provide new opportunities to investigate the interactions between a biota and glacial environments. Copyright © 2010 by the American Geophysical Union.